Trends in Insecticide Resistance in Natural Populations of Malaria Vectors in Burkina Faso, West Africa: 10 Years’ Surveys - Dabiré, K. R.; Diabaté, A.; Namountougou, M.; Djogbenou, L.; Wondji, C.; Chandre, F.; Simard, F.; Ouédraogo, J-B.; Martin, T.; Weill, M.; Baldet, T. (IntechOpen, 2012)
None